Case reportDouble diagnosis of coronary artery disease and left ventricular non-compaction – case study - Dzielińska, Zofia; Petryka, Joanna; Kuśmierczyk, Mariusz; Skwarek, Mirosław; Demkow, Marcin (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
We present a rare case of double diagnosis of coronary artery disease and left ventricle non-compaction (LVNC) treated successfully with coronary artery bypass graft operation on the basis of viability assessment by cardiac magnetic resonance (CMR). A 71-year-old patient with a history of previous myocardial infarction of the inferior wall was admitted to our centre with pulmonary oedema following worsening symptoms of heart failure over the previous several days. Echocardiography revealed widely spread regional wall motion abnormalities with decreased left ventricular global function and hypertrabeculations of the inferior and posterior wall suggesting left ventricular non-compaction. Cardiac magnetic resonance confirmed the diagnosis of LVNC and demonstrated preserved viability of all myocardial segments. The patient underwent a successful coronary artery bypass graft operation. In the follow-up CMR study an improvement in left ventricular systolic function with sustained hypertrabeculation of the myocardium was reported. With the improvement of imaging techniques we are seeing even more cases of LVNC in clinical practice while the ultimate diagnostic criteria have not been established and its management remains a controversy. In the presented case of a 71-year-old man the patient improved greatly after revascularization. The morphology and viability of the myocardium were assessed accurately with CMR, which is a powerful diagnostic tool increasingly often used for everyday clinical decisions.